Aplikasi Dashboard Management System of Inventory Managment Pada PT. Semen Indonesia (Persero)Tbk - Wardani, Marina Kusuma; Setyawan, Henry Bambang; Romeo, Romeo (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
PT. Semen Indonesia is company in industry of cement, the process of making cement necessary some process that combustion raw mix/ slurry be clinker. grinding clinker, and gypsum to be semen. The process of monitoring above required to control limited supply of the raw material used to production process, due to the lack of information that still appears related the amount of stock of raw materials required and the amount of the stock of raw materials used for production, so that the possibility of a buildup and lack of raw materials at the time of production often occurs. Dashboard is an application that can be used for monitoring company stock inventory in real time. The information shown in the dashboard in this application in the form of graphics information tailored to key performance indicator (KPI) from the company, This application can display a graph of the trend of value and quantity of supplies per month, showing total receipt per month, showing a graph of the trend of total consume which is used in the production process monthly, showing a graph of the trend of Inventory Turnover (ITO, total consume, and aging material.